Examining the effects of prekindergarten to second grade classroom quality on early elementary achievement - Kara, Yusuf; Farmer, Dylan E.; Wright, Annie; Kamata, Akihito; Hujar, Julia; Baker, Scott K. (Frontiers in Education, 2024)
Previous research has investigated the influence of preschool interventions in early elementary environments with some results suggesting that high quality early preschool experiences may have meaningful effects on student academic outcomes not only immediately following the preschool years but also in the long term. This study aimed to investigate this topic further by using a novel cross-classified model to account for the complex hierarchical structure of a largescale longitudinal and multilevel dataset. First, we examined the carryover classroom effects from prekindergarten (PK), kindergarten (K), and first grade on later grades' reading and mathematics scores. Second, we explored the effect of PK to second grade classroom quality on students' K, first, and second grade reading and mathematics scores. Our analyses yielded significant PK carryover classroom effects for reading; these results provide evidence that a student's PK classroom continues to impact that student for at least three years after.Additionally, one domain of PK classroom quality -classroom organization-was found to be positively related to students' K, first, and second grade reading outcomes.